Utilization of Banana (Musa Sapientum) pith as extender in chicken longaniza - Ruales, Sheila Marie Espinosa (2000.)
The use of banana pith as an extender in chicken longanisa was investigated and was found to be technically and economically feasible.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Banana pith; Musa Sapientum; Chicken Longaniza